Recurrent fires and environment shape the vegetation in Quercus suber L. woodlands and maquis. - Schaffhauser, Alice; Curt, Thomas; Véla, Errol; Tatoni, Thierry (Comptes rendus biologies, 2012)
The effects of fire recurrence on vegetation patterns in Quercus suber L. and Erica-Cistus communities in Mediterranean fire-prone ecosystems of south-eastern France were examined on stands belonging to 5 fire classes, corresponding to different numbers of fires (from 0 to 4) and time intervals between fires since 1959. A common pool of species was identified among the plots, which was typical of both open and closed maquis. Fire recurrence reduced the abundance of trees and herbs, whereas it increased the abundance of small shrubs. Richness differed significantly between the most contrasting classes of fire recurrence, with maximal values found in control plots and minimal values in plots that had burned recurrently and recently. Equitability indices did not vary significantly, in contrast to Shannon's diversity index which mostly correlated with richness. Forest ecosystems that have burnt once or twice in the last 50 years were resilient; that is to say they recovered a biomass and composition similar to that of the pre-fire state. However, after more than 3-4 fires, shrubland communities displayed lower species richness and diversity indices than unburned plots. The time since the last fire and the number of fires were the most explanatory fire variables, governing the structure of post-fire plant communities. However, environmental factors, such as slope or exposure, also made a significant contribution. Higher rates of fire recurrence can affect the persistence or expansion of shrublands in the future, as observed in other Mediterranean areas.
The following values have no corresponding Zotero field: accession-num: 22721564
Keywords: Acidic soil; biomass; climate; cork-oak; Ecosystem; Erica arborea L.; Fire recurrence; Fires; France; Mediterranean Region; Plant communities; Plants; Plants: classification; Quercus; Seasons; Species Specificity; Trees

The effect of cork removal on the radial growth and phenology of young cork oak trees - Fialho, C.; Lopes, F.; Pereira, H. (Forest Ecology and Management, 2001)
The effect of the removal of cork was studied in 11-years old cork oak trees (Quercus suber L.), growing in favorable conditions, in relation to phenology and radial growth during two years. Longevity of leaves was 14±15 months (1996, 1998) and 10 months (1997). Bud burst started in mid-February and leaf ¯ushing in April, extending until June. Neither a distinct two-period ¯ushing nor an autumn bud burst or leaf ¯ushing were observed. Radial growth started in mid-April and continued until the end of November, with the maximum growth in June and July. In trees with the removal of cork, leaf abscission occurred a little earlier and new branches had on average 23% fewer new leaves. The radial growth of the trees and its general seasonal pattern were not affected by cork removal in the year of removal or in the year after. The only observation was a shift of the maximum radial growth rate from June to July for the trees where cork had been removed
Keywords: cork removal; cork-oak; Phenology; Quercus suber; Radial growth

The effect of cork removal on the radial growth and phenology of young cork oak trees - Fialho, C; Lopes, F; Pereira, H (Forest Ecology and Management, 2001)
The effect of the removal of cork was studied in 11-years old cork oak trees (Quercus suber L.), growing in favorable conditions, in relation to phenology and radial growth during two years. Longevity of leaves was 14±15 months (1996, 1998) and 10 months (1997). Bud burst started in mid-February and leaf ¯ushing in April, extending until June. Neither a distinct two-period ¯ushing nor an autumn bud burst or leaf ¯ushing were observed. Radial growth started in mid-April and continued until the end of November, with the maximum growth in June and July. In trees with the removal of cork, leaf abscission occurred a little earlier and new branches had on average 23% fewer new leaves. The radial growth of the trees and its general seasonal pattern were not affected by cork removal in the year of removal or in the year after. The only observation was a shift of the maximum radial growth rate from June to July for the trees where cork had been removed
Keywords: cork removal; cork-oak; Phenology; Quercus suber; Radial growth

Análisis del área foliar del alcornoque en relación con tratamientos silvo-pastorales - Caritat, A. I.; Molinas, M. I.; Vilar, I. P.; Masson, L. (Scientia gerundensis, 1999)
The fluctuations showed by ecophysiologic parameters, like leaf area and leaf area indices, in relation to silvo-pastoral treatments can be used to evaluate the effects of these treatments on o&-cork forests. Leaf area shows a close relation to production and is a good indicator of the physiological state of the plants. Leaf area, leaf area indices and specific leaf weight have been studied in four cork-oak wood stations in relation to shrub clearing and grazing treat- ments. Leaf parameters have been measured using a computer image analysis system. We found that, in general, leaf average area is increased by silvo-pastotal treatments, apparently in order to recover the wasted canopy and in answer to nutrient supply. On the other hand, leaf area index decreases after treatments because of the leaf biomass lost, but the fast apical growth showed by cork-trees in treated plots points to a quick recovery of this parameter when an appropiate tree density is reached.
Keywords: cork-oak; Grazing; leaf area; leaf index; shrub cleareing; silvo-pastoral treatments

Análisis del área foliar del alcornoque en relación con tratamientos silvo-pastorales - Caritat, A I; Molinas, M I; Vilar, I P; Masson, L (Scientia gerundensis, 1999)
The fluctuations showed by ecophysiologic parameters, like leaf area and leaf area indices, in relation to silvo-pastoral treatments can be used to evaluate the effects of these treatments on o&-cork forests. Leaf area shows a close relation to production and is a good indicator of the physiological state of the plants. Leaf area, leaf area indices and specific leaf weight have been studied in four cork-oak wood stations in relation to shrub clearing and grazing treat- ments. Leaf parameters have been measured using a computer image analysis system. We found that, in general, leaf average area is increased by silvo-pastotal treatments, apparently in order to recover the wasted canopy and in answer to nutrient supply. On the other hand, leaf area index decreases after treatments because of the leaf biomass lost, but the fast apical growth showed by cork-trees in treated plots points to a quick recovery of this parameter when an appropiate tree density is reached.
Keywords: cork-oak; Grazing; leaf area; leaf index; shrub cleareing; silvo-pastoral treatments

Stress proteins co-expressed in suberized and lignified cells and in apical meristems - Pla, Maria; Huguet, Gemma; Verdaguer, Dolors; Puigderrajols, Pere; Llompart, Blanca; Nadal, Anna; Molinas, Marisa (Plant Science, 1998)
We report the cloning of a small heat shock protein, Qs –HSP17, and an osmotin like protein, Qs –OLP, from cork oak phellem tissue (cork cells). Both genes are expressed in suberizing cells and in other cells subject to endogenous stress associated with free radicals. We provide evidence that smHSPs and OLPs accumulate in overwintering buds and speculate that their role is similar to that in seed dormancy. We also show that both stress proteins are mainly located in the region of the quiescent center in root apex and in central meristem in the shoot apex. We emphasize that smHSPs and OLPs are expressed in cells growing under endogenous stress or facing long life-span. We discuss a possible role of these stress proteins against oxidative stress
Keywords: cork-oak; osmotin like proteins; phellem; Quercus suber; small heat shock proteins; tissue specificity

Clasificación ecológica y caracterización selvícola y PRODUCTIVA DEL PARQUE NATURAL DE LOS ALCORNOCALES (CÁDIZ y MÁLAGA) - Torres Álvarez, E; Montero González, G; V ÁZQUEZ PIQUÉ, F J (II Congreso Forestal Español, 1997)
An ecological classification of the Natural Park "Los Alcornocales" (Cádiz and Málaga, Spain) and a silvicultural and productive characterisation are done. The territorial c1assification is assisted by a Geographical Information System. Sixteen Territorial Classes and five classes of cork-oak potentiality are defined and mapped. Using a sample of seventy two plots, the cork-oak forests of this area are silvicultural and productively characterised, according their Territorial Class.
Keywords: Cork; cork-oak; Ecological classification; Geographical inforn1ation system; Potentiali ty; Quercus suber

Plan de calas de corcho y establecimiento de rodales selectos de alcornoque en andalucía - Carrasco, Angel; BORRERO, GUMERSINDO; CAMPAYO, P.; RODRIGUEZ, M.; ÁLVAREZ, J. Ma; FARIÑA, J. Ma; E. TORRES; Privado, Consultor; La, C. I.; Manojo, D. E. L.; Madrid, D. E. Rosas (II Congreso Forestal Español, 1997)
Since 1995, the "Consejería de Medio Ambiente" of the "Junta de Andalucía" has been developping a "Cork samples Plan and Establishment of select "Areas" of the Quercus suber". This plan is intended to collect technical-scientifical information, used both for a better knowledge of the cork oak forests and their principal product, cork, as well as for the elaboration of a cork quality map of the Andalusian Community. They also provide cork- tree owners with information about the explotation quality, for which cork samples are taken both from cork trees and from cork-piles. Using the collected samples, once they are classified and analised in the laboratory, and according to the data collected in the field, quality reports on cork are effec~ll(lted for the owner. Subsequently, these samples are show in a permanent exposition in thejaboratorywhere buyers or any other person interested can obtain information about the quality offered in the different Andalusian forests. Since 1995, the obtained information is also being used, amplifying the data taken referent to select "areas" of the cork oak forests to be able to establish a select "areas" network of Quercus suber capable of producing high quality acorns.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español
Keywords: Andalucía; Cork; cork-oak; Quercus suber; Select "areas"

Plan de calas de corcho y establecimiento de rodales selectos de alcornoque en andalucía - Carrasco, Angel; BORRERO, GUMERSINDO; CAMPAYO, P; RODRIGUEZ, M; ÁLVAREZ, J.Ma; FARIÑA, J.Ma; E.TORRES; Privado, Consultor; La, C I; Manojo, D E L; Madrid, D E Rosas (II Congreso Forestal Español, 1997)
Since 1995, the "Consejería de Medio Ambiente" of the "Junta de Andalucía" has been developping a "Cork samples Plan and Establishment of select "Areas" of the Quercus suber". This plan is intended to collect technical-scientifical information, used both for a better knowledge of the cork oak forests and their principal product, cork, as well as for the elaboration of a cork quality map of the Andalusian Community. They also provide cork- tree owners with information about the explotation quality, for which cork samples are taken both from cork trees and from cork-piles. Using the collected samples, once they are classified and analised in the laboratory, and according to the data collected in the field, quality reports on cork are effec~ll(lted for the owner. Subsequently, these samples are show in a permanent exposition in thejaboratorywhere buyers or any other person interested can obtain information about the quality offered in the different Andalusian forests. Since 1995, the obtained information is also being used, amplifying the data taken referent to select "areas" of the cork oak forests to be able to establish a select "areas" network of Quercus suber capable of producing high quality acorns.
Keywords: Andalucía; Cork; cork-oak; Quercus suber; Select "areas"

Relación entre la densidad de la masa y la producción de corcho en montes alcornocales del sur de españa - Álvarez, E. Torres; González, G. Montero; Suárez, M. A.; Cámara, D. E. L. A.; TORRES ÁLVAREZ, E.; Montero González, G.; Suárez de la Cámara, M. A. (II Congreso Forestal Español, 1997)
In this paper the influence of cork-oak stand density on quantity and quality cork production is studied. Seventy five experimental plots were installed at Cortes de la Frontera (Málaga, Spain) cork-oak forests. Sorne stand and productive variables for different basal area were studied. The statistical analysis of the data permit to propose 20-25 m2!ha basal area as the optimum stand density
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: cork-oak; Quercus suber; silviculture; stand density

Relación entre la densidad de la masa y la producción de corcho en montes alcornocales del sur de españa - Álvarez, E Torres; González, G Montero; Suárez, M A; Cámara, D E L A; Torres Álvarez, E; Montero González, G; Suárez de la Cámara, M A (II Congreso Forestal Español, 1997)
In this paper the influence of cork-oak stand density on quantity and quality cork production is studied. Seventy five experimental plots were installed at Cortes de la Frontera (Málaga, Spain) cork-oak forests. Sorne stand and productive variables for different basal area were studied. The statistical analysis of the data permit to propose 20-25 m2!ha basal area as the optimum stand density
Keywords: cork-oak; Quercus suber; silviculture; stand density

Seguimiento de la regeneración natural de alcornoque bajo condiciones microecológicas diferentes. - Torres Álvarez, E; Montero González, G; de la cámara, m. a. (II Congreso Forestal Español, 1997)
This paper studies the natural regeneration of cork-oak in the forests of Aljibe mountains (Málaga, Spain). A plot for monitoring the development of cork-oak seedlings was installed at Cortes de la Frontera cork-oak forests, under different microecological conditions. To get a plentiful and healthy stock of seedlings is necessary enclose the area and to have a light crown cover, is the main conclusion.
Keywords: cork-oak; natural regeneration; Quercus suber; Sylviculture

Variaçáo da porosidade da cortiça ao longo do tronco dosobreiro - Lopes, Fernando; Pereira, Helena (II Congreso Forestal Español, 1997)
The within tree variation of cork quality has practical relevance when considering the methodology for estimating the quality of production using a field sampling. Samples are usually taken at breast height and an indication how quality at this level might relate to the overall average quality would help to improve estimates for the overall stand cork quality. The porosity of cork was analysed for whole stems. A total of 12 trees were evaluated, from six sites (Mora, Palma, Porto Alto, Grandola, Azaruja and Chamusca). The porosity was measured using image analysis techniques in tangential sections and in transverse sections. The cork for the different trees observed had different average porosities, ranging from 2.7% to 14.5% in the transverse section at b.h .. Within tree variatíon of cork porosity was found, with a average pattern of decreasing porosity within tree height. However a umque pattern of variation could not be established.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Cork; cork-oak; image analysis; Porosity; stem

Variaçáo da porosidade da cortiça ao longo do tronco dosobreiro - Lopes, Fernando; Pereira, Helena (II Congreso Forestal Español, 1997)
The within tree variation of cork quality has practical relevance when considering the methodology for estimating the quality of production using a field sampling. Samples are usually taken at breast height and an indication how quality at this level might relate to the overall average quality would help to improve estimates for the overall stand cork quality. The porosity of cork was analysed for whole stems. A total of 12 trees were evaluated, from six sites (Mora, Palma, Porto Alto, Grandola, Azaruja and Chamusca). The porosity was measured using image analysis techniques in tangential sections and in transverse sections. The cork for the different trees observed had different average porosities, ranging from 2.7% to 14.5% in the transverse section at b.h .. Within tree variatíon of cork porosity was found, with a average pattern of decreasing porosity within tree height. However a umque pattern of variation could not be established.
Keywords: Cork; cork-oak; image analysis; Porosity; stem

Annual cork-ring width variability of Quercus suber L. in relation to temperature and precipitation (Extremadura, southwestern Spain) - Caritat, A; Molinas, M; Gutiérrez, E (Forest Ecology and Management, 1996)
A 14 year sequence of cork-ring width chronology is correlated with rainfall and temperature data. Cork specimens were obtained from three cork peel samplings carried out in 1989, 1991 and 1993 from a cork ‘dehesa’ in Ckeres, Spain. Average width of cork-rings varied between 2.05 and 4.37 mm. The cork-ring width chronologies of the three peel-off samplings show definite agreement patterns. Differences in ring width in years of greater and lesser growth are clearly marked. Correlation between ring width and rainfall indicates that the rain periods with the greatest influence on cork growth are those occurring from November to June, followed by those from November to September. Temperature, on the other hand, shows a negative correlation with cork growth, except during the coldest months and the months of April and September when temperature possibly has a crucial influence on phellogen activation.
Keywords: climatic fluctuations; cork growth; cork-oak; cork-ring chronology; Quercus suber L.

Annual cork-ring width variability of Quercus suber L. in relation to temperature and precipitation (Extremadura, southwestern Spain) - Caritat, A.; Molinas, M.; GUTIÉRREZ, E. (Forest Ecology and Management, 1996)
A 14 year sequence of cork-ring width chronology is correlated with rainfall and temperature data. Cork specimens were obtained from three cork peel samplings carried out in 1989, 1991 and 1993 from a cork ‘dehesa’ in Ckeres, Spain. Average width of cork-rings varied between 2.05 and 4.37 mm. The cork-ring width chronologies of the three peel-off samplings show definite agreement patterns. Differences in ring width in years of greater and lesser growth are clearly marked. Correlation between ring width and rainfall indicates that the rain periods with the greatest influence on cork growth are those occurring from November to June, followed by those from November to September. Temperature, on the other hand, shows a negative correlation with cork growth, except during the coldest months and the months of April and September when temperature possibly has a crucial influence on phellogen activation.
Keywords: climatic fluctuations; cork growth; cork-oak; cork-ring chronology; Quercus suber L.

Are ecophysiological responses influenced by crown position in cork-oak? - Oliveira, G; Werner, C; Correia, O (Ann. For. Sci., 1996)
Montados and dehesas of Quercus ilex and Quercus suber occupy large areas in the Iberian Peninsula and are characterized by a low-density tree cover. The variability of responses within tree canopies in such open stands has been little studied. We investigated the variation of stomatal conductance within the crown of a cork-oak (Q suber L), by studying its diurnal and seasonal courses at two different heights and four directions within the canopy. Height did not strongly affect leaf response, as a consequence of the crown structure. Differences were found in microclimatic conditions and maximum stomatal conductance among directions. However, overall daily stomatal conductance was similar among different crown sections, suggesting that leaves develop different mechanisms to accomodate the microclimatic constraints which affect the particular position they occupy in the crown of cork-oak.
Keywords: cork-oak; isolated tree; microclimate; Stomatal conductance; within-crown variability

Are ecophysiological responses influenced by crown position in cork-oak? - Oliveira, G; Werner, C; Correia, O (Ann. For. Sci., 1996)
Montados and dehesas of Quercus ilex and Quercus suber occupy large areas in the Iberian Peninsula and are characterized by a low-density tree cover. The variability of responses within tree canopies in such open stands has been little studied. We investigated the variation of stomatal conductance within the crown of a cork-oak (Q suber L), by studying its diurnal and seasonal courses at two different heights and four directions within the canopy. Height did not strongly affect leaf response, as a consequence of the crown structure. Differences were found in microclimatic conditions and maximum stomatal conductance among directions. However, overall daily stomatal conductance was similar among different crown sections, suggesting that leaves develop different mechanisms to accomodate the microclimatic constraints which affect the particular position they occupy in the crown of cork-oak.
Keywords: cork-oak; isolated tree; microclimate; Stomatal conductance; within-crown variability

Litterfall and mineral return in two cork-oak forests in northeast spain - Caritat, A.; Bertoni, G.; Molinas, M.; Oliva, M.; Domínguez-Planella, A. (Ann. For. Sci., 1996)
Seasonal trends in littertall and potential mineral return were studied in two cork-oak forest sites in the northeastern Iberian peninsula. The estimated average litter production was 3.9 Mg.ha-1.year -1 for one site and 4.6 Mg.ha-1.year-1 for the other; these figures are similar to those reported for holm-oak (Quercus ilex) forests in the same area. Seasonal litterfall patterns were typical of Mediterranean forest ecosystems. Leaves accounted for 46 to 78% of the total dry matter. Their annual weighted-average mineral composition was low in macronutrients (N 8-9; K 4-5; Mg 0.8-1.3; Ca 9-10 and P 0.4-1 mg.g-1) and relatively high in micronutrients such as Mn (2-2.2 mg.g-1) or Fe (0.3-0.4 mg.g-1). Minimum N and P concentrations were found during the growth period. Estimates of potential mineral return for an annual cycle were N 38-52, P 2.1-5.2, K 20-28, Ca 44-53 and Mg 5.4-5.0 kg.ha -1, depending on the site biomass and fertility.
Keywords: cork-oak; litterfall; Mediterranean forest ecosystems; nutrient cycling; Quercus suber

Litterfall and mineral return in two cork-oak forests in northeast spain - Caritat, A; Bertoni, G; Molinas, M; Oliva, M; Domínguez-Planella, A (Ann. For. Sci., 1996)
Seasonal trends in littertall and potential mineral return were studied in two cork-oak forest sites in the northeastern Iberian peninsula. The estimated average litter production was 3.9 Mg.ha-1.year -1 for one site and 4.6 Mg.ha-1.year-1 for the other; these figures are similar to those reported for holm-oak (Quercus ilex) forests in the same area. Seasonal litterfall patterns were typical of Mediterranean forest ecosystems. Leaves accounted for 46 to 78% of the total dry matter. Their annual weighted-average mineral composition was low in macronutrients (N 8-9; K 4-5; Mg 0.8-1.3; Ca 9-10 and P 0.4-1 mg.g-1) and relatively high in micronutrients such as Mn (2-2.2 mg.g-1) or Fe (0.3-0.4 mg.g-1). Minimum N and P concentrations were found during the growth period. Estimates of potential mineral return for an annual cycle were N 38-52, P 2.1-5.2, K 20-28, Ca 44-53 and Mg 5.4-5.0 kg.ha -1, depending on the site biomass and fertility.
Keywords: cork-oak; litterfall; Mediterranean forest ecosystems; nutrient cycling; Quercus suber

Crecimiento radial del corcho de reproducción de los alcornocales catalanes y valencianos - Fos, S.; Barreno, E. (Scientia gerundensis, 1994)
Eastern cork-oak forests are present in territories with different environmental characteristics, allowing to raise comparative studies between them. This work is an attempt to evaluate the radial growt differences of the reproduction cork, using tschniques of optical microscopy, having developed a new methodology. Thus, severa1 sites from catalonian and valencian cork-oak forests have been selected. In the quantification of this growth, the contribution of each cork type (early cork and late cork) in the annual growing rings have been differentia- ted. The annual increments measwed in catalonian corks have an average of 2.958 mm, being a bit lower in Castell6n with 1.622 mm. These differences in the annual growing rings are due to the early development higher in catalonian cork (2.623 mm) than in valencian ones (1.235 mm), late cork thickness is similar in the two areas. These differences seem to be related with the escarce summer dry period in catalonian cork-oak forests. Important anato- mical differences related with the mentioned ombroclimatic asimetries have been observed too.
Keywords: Anatomy; bioclimatology; cork-oak; Quercus suber L.; Radial growth

Crecimiento radial del corcho de reproducción de los alcornocales catalanes y valencianos - Fos, S; BARRENO, E (Scientia gerundensis, 1994)
Eastern cork-oak forests are present in territories with different environmental characteristics, allowing to raise comparative studies between them. This work is an attempt to evaluate the radial growt differences of the reproduction cork, using tschniques of optical microscopy, having developed a new methodology. Thus, severa1 sites from catalonian and valencian cork-oak forests have been selected. In the quantification of this growth, the contribution of each cork type (early cork and late cork) in the annual growing rings have been differentia- ted. The annual increments measwed in catalonian corks have an average of 2.958 mm, being a bit lower in Castell6n with 1.622 mm. These differences in the annual growing rings are due to the early development higher in catalonian cork (2.623 mm) than in valencian ones (1.235 mm), late cork thickness is similar in the two areas. These differences seem to be related with the escarce summer dry period in catalonian cork-oak forests. Important anato- mical differences related with the mentioned ombroclimatic asimetries have been observed too.
Keywords: Anatomy; bioclimatology; cork-oak; Quercus suber L.; Radial growth

Ecological aspects of the floral phenology of the cork-oak (Q suber L): why do annual and biennial biotypes appear? - Elena-Rossello, J A; de Rio, J M; Valdecantos Garcia, J L; Santamaria, I G (Ann. For. Sci., 1993)
Phenological observations (periods of flowering and pollination, floral structures, etc) were made over a 3-year period in natural populations of Q suber. We demonstrated the existence of 2 different types of seed cycles in the cork-oak. The 'annual biotype', requires only 1 season to complete its reproductive cycle (ie, similar to that of the Lepidobalanus group), whereas the 'biennial biotype' requires 2 full years (similar to Erythrobalanus). The variability observed in the cork-oak, during the reproductive cycle, and the meaning of the existence of 2 different reproductive strategies in the same species, are discussed
Keywords: annual and biennial biotypes; cork-oak; ecological variability; floral phenology; Quercus; reproductive strategies

Ecological aspects of the floral phenology of the cork-oak (Q suber L): why do annual and biennial biotypes appear? - Elena-Rossello, J. A.; de Rio, J. M.; Valdecantos Garcia, J. L.; Santamaria, I. G. (Ann. For. Sci., 1993)
Phenological observations (periods of flowering and pollination, floral structures, etc) were made over a 3-year period in natural populations of Q suber. We demonstrated the existence of 2 different types of seed cycles in the cork-oak. The 'annual biotype', requires only 1 season to complete its reproductive cycle (ie, similar to that of the Lepidobalanus group), whereas the 'biennial biotype' requires 2 full years (similar to Erythrobalanus). The variability observed in the cork-oak, during the reproductive cycle, and the meaning of the existence of 2 different reproductive strategies in the same species, are discussed
Keywords: annual and biennial biotypes; cork-oak; ecological variability; floral phenology; Quercus; reproductive strategies

Effect of in vitro cold storage on surviving and proliferation of cork-oak (Quercus suber L.) cultures - Romano, A; Noronha, C; Martins-Loução, M a (Congreso Forestal Español, 14 e 18 Junho de 1993, Lourizán, 1993)
Cork-oak cultures were stored in vitro without na intervening subculture, at 5º C in the dark for 5 months without loosing their capacity to regenerate when subcultured under standard conditions. The viability, proliferation rate and elongation of the explants were evaluated during 5 months of storage. Proliferation rate of stored cultures was observed during 5 months of storage. Proliferation rate of stored cultures was observed during the following 3 profileration cycles and compared to unstored controls of the same age. Shoot cultures survived with 100% viability and the proliferation rate was not statistically different from the controls. The results here described indicate the feasibility of establishing na in vitro active gene bank for Quercus suber.
Keywords: Cold storage; cork-oak; Germplasm; Medium-term storage; micropropagation; Quercus suber L.

INFLUENCIA DE LA DENSIDAD DE LA MASA EN LA CALIDAD Y PRODUCCION DE CORCHO EN LOS ALCORNOCALES DE CORTES DE LA FRONTERA (MALAGA) - Montero, G; TORRES, E; Suárez, M A; Ortega, C (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The influence of stand density on cork yield was evaluated for the Cortes de la Frontera (Spain) cork oak stand. Fifty five experimental plots were installed. The modular values of several variables which define cork oak yield potential of a tree, are presented by stand densitY'clusters (basal area groups). Likewise, many stand variables for different basal areas were studied
Keywords: cork-oak; silviculture; stand density

El crecimiento radial del alcornoque en cinco parcelas de alcornocal de Girona - Caritat, A.; Molinas, M.; Oliva, M. (Scientia gerundensis, 1992)
Tree rings of Quercus suber L. are porous and difficult to read because of the irregular growth rhythm. Radial growth has been measured in five experimental plots situated in the region of Girona (Catalonia, NE Spain). Cores of ten standard trees of each plot were extracted using a Pressler borer. In three plots woody disks from standard trees were also obtained. Tree rings were examinated under binocularlens. The CATRAS computer program (Anio1,1983 ) was used to find statistical parameters. Tree rings have an average width changing from 1,21 to 3,74 mm, while average standard deviation varies from 0,24 to 1,88 mm. and autocorrelation from 0,008 to 0.894 . These values are similar to those found in other Mediterranean Quercus, like Q. ilex L. The studied cork-oak plots ,with diametrical classes between 5 and 57 cm, show regular growth characteristic of young forest. The St. Hilari plot has the maturest trees, (diametrical classes from 24 to 57 cm) and this fact was reflectedin thegrowthcurve. Suddengrowthincreases are attributed to forestry management measures like clearing or selective cutting down. The effects of periodic cork extractions could no be clearly appreciated in this study.
Keywords: cork-oak; Mediterranean sclerophylls; Quercus suber L.; Radial growth; wood rings

Estudos de hidrologia em povoamentos de Quercus suber e caracterizaçao mesológica do ecossistema - Almeida, A. P. (Scientia gerundensis, 1992)
The main objective of the project is to assess the effect of different types of soil management under cork-oak tree stands on water use and cork productivity. The study utilized a 5.5 ha watershed near the town of Mora, center of Portugal. The watershed contained scattered cork- oak with natural pasture, which is probably the most representative formof landuse in the region. de 1990, que va mostrar la The project used the basic water balance equation, being evaluated incident rainfall, runoff, evapotranspiration and changes in soil water storage. Measurements of the tree stands and canopies were included for the characterization of throughfall and stemflow. Interception was estimated to evaluate its effects onrainfallredistribution and onthe dynarnics of evapotranspiration. Collection of data for the intensive hydrologic study begun in October 1, 1988. During 1989, surface runoff was 10.8 percent of annual rainfall. For the same period, canopy interception by the Quercus suber stand was 15.4 percent and throughfall accounted for 84.6 percent of annual rainfall, as stemfiow was considered negligible. Statistical analysis of data related to the period January, 1990 to May, 1990 is now being undertaken. Itis apparent, however, from the study, that the data sets should be extended through further research to confirm the tentative hydrological trends of the first period.
Keywords: cork-oak; land use; pasture; productivity; water balance

Evidence for hybridization between sympatric holm-oak and cork-oak in Spain based on diagnostic enzyme markers - Elena-Rossello, J. A.; Lumaret, R.; Cabrera, E.; Michaud, H. (Plant Ecology, 1992)
Hybridization has been detected in mixed populations of juvenile cork-oak and holm-oak individuals using three diagnostic enzyme loci coding for esterases, leucine amino peptidases and acid phosphatases respectively. Among the 35 studied individuals, 29, 5 and 1 were identified as holm-oak, cork-oak and hybrid respectively. Such diagnostic markers are likely to be useful to detect and remove hybrids at the juvenile stage in areas where the holm-oak is grown for acorn production and the cork-oak is cultivated for cork. This is necessary since hybrid adults produce neither cork nor acorns of high quality.
Keywords: cork-oak; enzyme markers; holm-oak; Hybridization; Quercus

Influence of Growth Regulators on Shoot Proliferation in Quercus suber L. - Romano, A; Noronha, C; Martins-Loução, M a (Annals of Botany, 1992)
Procedures have been developed to standardize the multiplication stage during mature cork-oak (Quercus suber L.) micropropagation. Axillary and terminal buds were established on Gresshoff and Doy basal medium containing 1 mg I−1 of 6-benzylaminopurine (BAP). Initiation of cultures was possible all over the year. The effects of BAP, Z, IBA, 1AA and NAA and various nutrient formulae on shoot growth and proliferation was investigated. BAP was more suitable than zeatin. Shoot proliferation and elongation were strongly improved by the combination BAP/IAA in the presence of low salt media, like Gresshoff and Doy or Woody Plant medium. Both rates were significantly increased when a double-phase culture system was used. Shoots have been multiplied for 1 year at the rate of three to four-fold every 4 weeks without any decline of vigour. Rooting was achieved by briefly dipping the basal ends of in vitro regenerated shoots in an IBA concentrated solution. The results here reported constitute a promising step towards large scale in vitro propagation of a species in which conventional vegetative propagation by cuttings is very difficult.
Keywords: Auxins; browning; cork-oak; cytokinins; Forestry; multiplication; Quercus suber L.; re-invigoration; re-multiplication; two-phase medium

Micropropagation of mature cork-oak (Querqus suber L.): establishment problems - Romano, A; Martins-Loução, M a (Scientia gerundensis, 1992)
Procedures have been developed to standardize the establishment stage during mature cork-oak (Quercus suber L.) micropropagation. Axillary and terminal buds cultured in Gresshof and Doy (1972) (GD) medium were used as first explant. Establishment of cultures was very difficult due to browning of the tissue and/or the medium and bacterial contamination. Browning problems, probably due to phenolic compounds exudation of the primary explant, were found to be higher in winter. Nevertheless, initiation of cultures was possible all over the year, presumably due to the preconditioning of cuttings. Explants were established in a GD medium containing 6-benzlaminopurine (BAP) 1 mgl-1. Every 4 weeks the cultures were subcultured to the same GD medium and induced to proliferate being 4:1 the multiplication rate. Shoots were induced to elongate by decreasing BAP concentration. In vitro rooting on agar-solidified medium suplemented with 1 mgl-1 indolacetic acid (IAA) gave the best results. Liquid medium (sorbarod system) and in vivo rooting were also assayed.
Keywords: browning; contaminants; cork-oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture

Histology of Callogenesis and Somatic Embryogenesis Induced in Stem Fragments of Cork Oak (Quercus suber) Cultured In Vitro - MAÂTAOUI, M E L; Espagnac, H; MICHAUX-FERRIÈRE, N (Annals of Botany, 1990)
Calluses able to produce somatic embryos were formed during in vitro culture of shoot fragments of cork oak (Quercus suber L.).Histological monitoring of these fragments during culture showed that it was the cortical parenchyma cells which underwent dedifferentiation before calluses were formed by repeated divisions. The calluses consisted of parenchyma cells surrounded by a few layers of meristematic cells. Proembryos formed in groups around the edge of some calluses. Histological examination showed that they were produced by the evolution of two different categories of cell: one category had the appearance of ‘embryogenic’ cells with very thick walls, a small vacuole rich in starch and a well-developed nucleus with a prominent nucleolus. The other cells were very bulky with large vacuoles; their morphology was similar to that of suspensor cells encountered in embryogenesis in gymnosperms. The ontogenic stages were similar to those described in zygotic embryos of the genus Quercus. Nevertheless, most of the embryonic structures deviated from normal development and at all stages produced secondary proembryos.
Keywords: callogenesis; cork-oak; embryogenic cells; histology; Quercus suber L.; secondary embryogenesis; Somatic embryogenesis; starch

Cultivo in vitro del alcornoque - TORIBIO, M; CELESTINO, C (Scientia gerundensis, 1989)
Vegetative plant propagation is mainly used in the operational line of Forest Tree Improvement Programs to capture all the genetic potential, including the non-additive component of the genetic variance. In the case of genus Quercus, it could be also used to avoid the problems derived from installation and yielding of seed orchards. The tissue culture based micropropagation arises as an alternative technique to solve the problems of space and time associated with the classical techniques of asexual propagation. This article reviews the work done with cork-oak in this field. Up to date there are few papers dealing with in vitro culture of Quercus suher L. Embryo culture has been tryed to determine the minimum requeriments of the species and its morphogenic potential. Plantlet regeneration has been obtained following axillary budding on nodal segments from juvenile and rejuvenated tissues, elongation and rooting of microcuttings. Main problems arise on transplanting soil the neoformed plants. Callus culture has been achieved from cotyledons and epicotyl segments from young seedlings. In booth cases also somatic embryogenesis has been reported. This fact opens a new way for micropropagating cork-oak, which is discussed.
Keywords: cork-oak; micropropagation; plant regeneration; Quercus suber L.; Somatic embryogenesis; tissue culture

Efectos en el rendimiento de la produccion de corcho al modificar el calibre de las planchas taponables - González Fernández, T; Al, D E Corcho; El, Modificar; Fernández, T González (Scientia gerundensis, 1989)
The main purpose of this paper is to analise the posible effects of a diminution on the caliber of the bottle-cork on the economic profitability of the Extremadura cork-oak forest. A reduction from 22 mm to 17 mm in the wine-bottle neck will supose an increment of 27% in the raw production of bottle-cork.
Keywords: Cork; Cork Production; cork-oak; wine bottle neck

Estudio preliminar del crecimiento del alcornoque en la fase juvenil. - Oliva, M; Molinas, A Caritat M; Caritat, A; Molinas, M (SCIENTIA gerundensis, 1989)
Shoot elongation has been measured in two different groups of juvenil cork-oaks (Quercus suber) by means of their budding segments. One group has got 14 seedlings three years old, proceeding from a forest nursery. The other group consistes in 17 sprouts of three and one years old from a bumed cork-oak forest. Buddings segments of the three- years old seedlings show an average elongation of 4,l cm. Sprouts are more vigorous; the three years old ones have an average value of segment elongation of 6,05 cm, and the one year old ones an average value of 15,3 cm. A decrease in elongation appears along the succesive buddings
Keywords: buds; cork-oak; Quercus suber; shoot elongation; sprouts

ORGANIZACION Y VARIACIONES ESTACIONALES DEL ÁPICE VEGETATIVO DEL ALCORNOQUE - Molinas, M; Oliva, P; Vázquez, M Oliva P (Scientia gerundensis, 1989)
This paper is directed to the basic understand of organization and seasonal changes in the vegetative buds of the cork-oak through the study of the phenology and the histology of a branch during to annual cycles. During the period under study, two sprouting seasons succeded each year; one sprouting was allways in the middle of the spring and the other one either in the summer or in the fall. The elongation of the branch segments was characteristic of a cork-oak in juvenil phase. The hight value of the whole growth should be noticed. The cork oak produces both short and long shoots. Long shoots occur at the apex and distal portions of branches. The long and short shoots differ in number of leaves but not in internode elongation. Elongation depend on the shoot vigor and position. There is a good correlation between elongation and number of leaves per segment. Buds show seasonal changes. A rest phase, a bud expansion phase and a new bud formation phase partially omerlaping the bud expansion phase can be distinguished. Cork-oak vegetative buds show a tunica and corpus type of cellular zonation which corresponds to the Type I of the Gifford and Carson (1971) classification. Only lowermost leaves ovenvinter in the bud. This may explain the maked heteroblastia of the leaves in the shoots. The seasonal study shows that maximum cytohistological zonation occurs near the end of rapid shoot elongation.
Keywords: bud morphology; cork-oak; Phenology; Quercus suber; shoot elongation

PARTICIPACION DE Diplopia sp. EN EL ESCALDADO DEL ALCORNOQUE - Oliva i Estanyol, M; Molinas de Ferrer, M L (Scientia gerundensis, 1986)
This paper describes the association of Diplodia sp., a Sphaeropsidal fungus, with a new form of (<escaldat)) (dieback associated with trunk lessions) that we call <xancre secu (dry canker) in the cork-oak, Quercus suber L. The dry canker is a complex syndrome consisting of wilting and trunk canker lessions. The disease occurs in an acute form and then the tree dies quickly after cork removal; or it can follow an insidious form and the tree can react and form several layers of cork before dying. A description of the simptomatology is given. The fungus Diplodia sp. is isolated from diseased trees and it has infectious capatity on the living tissues. The isolate has conidial characteristics that slightly differ from other Diplodia parasitic in Quercus. Because the taxonomic revision of the genus is lacking we have not given an species name. The relation between ecological stress and disease is emphasized and some possible preventive measures are given.
Keywords: canker; cork-oak; forest pathology; Quercus suber L.; wilt

LIMITACIONES A LA REGENERACIÓN NATURAL DE LOS ALCORNOCALES EN EL PARQUE NACIONAL DE DOÑANA (HUELVA, ESPAÑA) P.M. - VÁZQUEZ, P M; Suárez, M A; TORRES, E (II Congreso Forestal Español, 1977)
The possible limitations to the in several experiences natural regeneration of the Quercus suber L. in a guarded area (Doñana) are undertaken in this study. The outputs offer a global vision of the natural regeneration in the Doñana's National Park. The production of seeds the sanitary state of the hoisted and their plagues, the attack of the spineless on the fruits and the climate don't harm the process of the natural regeneration in the -forest of Q. suber L. However the animal pressure (mammals), and the load cattle are the two factor s that impede the natural regeneration of the cork oak in Doñana. Finally, different strategies are contributed in order to recuperate the cork oak: fence, sowing, plantation and descent of the pressure animal in the zone.
Keywords: cork-oak; Doñana; natural regeneration; Quercus suber L.; silviculture